2013
DOI: 10.1080/02772248.2013.770859
|View full text |Cite
|
Sign up to set email alerts
|

Sub-chronic exposure to carbendazim induces biochemical and hematological alterations in male goats

Abstract: The present investigation reports the effect of repeated (90 days) administration of carbendazim on the biochemical and hematological parameters in male goats. Carbendazim administered orally at a daily dose of 50 mg kg À1 body weight for 90 consecutive days resulted in increased plasma concentration of aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), gamma-glutamyl transferase (GGT), creatinine and albumin, while alkaline phosphatase (ALP) and glucose levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…An increase in Alt and AST was observed in sera of rats exposed to carbendazim. In accordance with this result, Waghe et al 2013 [28] reported that carbendazim administered orally to male goat at a daily dose of 50 mg·kg −1 body weight for 90 consecutive days resulted in increased plasma concentration of aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), gamma-glutamyl transferase (GGT), creatinine and albumin, while alkaline phosphatase (ALP) and glucose levels were decreased. It was reported that transaminases were considered to be a more sensitive measure in evaluating liver function and damage.…”
Section: Discussionmentioning
confidence: 76%
“…An increase in Alt and AST was observed in sera of rats exposed to carbendazim. In accordance with this result, Waghe et al 2013 [28] reported that carbendazim administered orally to male goat at a daily dose of 50 mg·kg −1 body weight for 90 consecutive days resulted in increased plasma concentration of aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), gamma-glutamyl transferase (GGT), creatinine and albumin, while alkaline phosphatase (ALP) and glucose levels were decreased. It was reported that transaminases were considered to be a more sensitive measure in evaluating liver function and damage.…”
Section: Discussionmentioning
confidence: 76%